“And then the Germans came to town”: The lived experiences of an interpreter in Finland during the Second World War - Kujamäki, Pekka (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
During World War II, both the Finnish Army and its ally Germany were dependent on mediation practices provided by military personnel or civilians in the linguistic, cultural and ideological intersections of the given conflicts. By drawing on two autobiographical manuscripts – one written immediately after the war and the other later in the 1990s – this article examines the experiences of a female civilian interpreter engaged by the German Army from 1942 to 1945. In addition to directing attention to ordinary people in wartime translational tasks, this article contrasts the value of such post-hoc accounts in the historical translation analysis against the constraints imposed on them through their embeddedness in a certain communicative situation. It shows, furthermore, how the change in this communicative situation imposes changes on the writer’s emotional involvement and how this change mirrors her own stance towards the given narrative framework.